Classroom environment & its Relation Cognitive motive and Reflective Thinking of university Student (Journal of the College of Education for Women, 2019)
The present research aims at the following:- Measure Classroom environment of university Student (research sample)- MeasureCognitive motive and Reflective Thinking of university Student (research Sample) .- In order to Know the relationship between the Scores of Classroom environment andScores of cognitive motive and Scores of Reflective Thinking of university Student(research Sample) .Sample of research consisted of (500) Students for both genders distrivbted upon tencolleges in Baghdad University , (5) Scientific Colleges , and (5) human Colleges , Samplewas chosen by using radom method Research instruments were three , Prepared by the researcher ,The first is to measureclassroom environment . The Second to measure Cognitive motive . The third to measureReflective Thinking .The research verified the Validity of measurements and their items were analyzedStatistically upon the sample consisted of (500) Students for both genders to extract thediscrimination power and the Validity of items . Reliadility was calculated by methodThe Alpha kronbache method for internal constanc.After fulfilling measurements preparations , the final application was applied upon the majorresearch Sample Consisted of (500) students of both genders. Number of Statistical methodswere used to answer of the research aims and hypotheses like person Coeffisient m (t-test) forone sample two vaeiance analysis , multiple declivity analysis , Scheffe .The most important result achievd by the researcher is that there is a Positive Conjunctiverelation of statistical significance between Classroom environment and cognitive motive, also there is a Positive relationship of statistical significance between classroomenvironmentand Reflectiv thinking .That the erea of interachtion of Students With each other and the Organaztion of the Lessonand Provide a list Supplies and teaching field interaction with Students and Contribute to itsclear and Signicant . The researcher set some recommendations and suggestions .